RANGSANG IDESIONAL DALAM MENGGUNAKAN PROPERTI PADA PEMBELAJARAN TARI KREASI MELAYU DI SMP NEGERI 5 MEDAN - Sri - Lestari; Yusnizar - Heniwati (Universitas Negeri Medan, 2021)
ABSTRACT-This study aims to describe the professional stimuli in using property in learning Malay dance creations in SMP Negeri 5 Medan. The theory used in this research is the professional excitatory theory and property theory. Professional stimulation according to Smith in Suharto (1985: 23), namely